Foundations of peace and harmony in families and communities: Insights from a TRUST, LEARN and CARE (TLC) framework - Alan Hayes; Margaret Freestone; Jamin Day (Sunan Kalijaga: International Journal of Islamic Civilization, 2019)
In a world riven by conflict, violent extremism and sectarian animosities, peace is in short supply. Promoting peace is, however, central to the great traditions of faith, including Islam. Contrary to their core precepts, fear, hatred and envy drive an evil mis-construal of the core tenets of these religions; the antithesis of their fundamental commitment to the promotion of tolerance, care and compassion.  Contemporary events defy comprehension and highlight the urgent need to find ways, especially within families and the communities in which they live, to counter radicalisation. Families, after all, ought to be key contexts for promoting dialogue, understanding and peace, consistent with the precepts of the Abrahamic religious traditions, and the Qur’anic focus on families that sees them as the forum for fulfilling the basic Islamic foundations of peace. Strong families build capable, caring and compassionate communities. The present paper briefly outlines a three-element model that might be usefully applied to better understand the processes of development of prosocial attitudes, beliefs and behaviours that are so vital for peaceful, constructive and compassionate co-existence; attributes that are so vitally needed in an increasingly multi-cultural, multi-ethnic and multi-faith world.  The elements are encapsulated in three conceptually linked acronyms: TRUST; LEARN; CARE or TLC. The trust, learn, care (TLC) framework has been developed from key principles in the new discipline of family studies. Global changes present many challenges for families and communities. This article concludes that a peaceful and harmonious future will be built on the foundations for dialogue and understanding that start in families and communities. Trust and tolerance, learning and teaching, caring and compassion are at the heart of acceptance of diversity, growth of understanding and promotion of respect for cultures, religions and beliefs.